Are Cognitive Changes in Hereditary Spastic Paraplegias Restricted to Complicated Forms? - Jacinto-Scudeiro, Laís Alves; Dariva Machado, Gustavo; Ayres, Annelise; Burguêz, Daniela; Polese-Bonato, Marcia; González-Salazar, Carelis; Siebert, Marina; Cavalcante França Jr., Marcondes; Olchik, Maira Rozenfeld; Morales Saute, Jonas Alex (Frontiers in Neurology, 2019)
Background: Little is known about the cognitive profile of Hereditary Spastic Paraplegias (HSP), where most scientific attention has been given to motor features related to corticospinal tract degeneration. Objectives: We aimed to perform a broad characterization of the cognitive functions of patients with pure and complicated HSP as well as to determine the frequency of abnormal cognitive performances in the studied subtypes. Methods: A two-center cross-sectional case-control study was performed. All individuals underwent cognitive assessment through screening tests (Mini Mental State Examination - MEEM and Montreal Cognitive Assessment - MOCA) and tests to assess specific cognitive functions (Verbal fluency with phonological restriction - FAS; Verbal categorical fluency - FAS-cat and Rey's Verbal Auditory Learning Test -RAVLT). Results: Fifty four patients with genetically confirmed HSP diagnosis, 36 with spastic paraplegia type 4 (SPG4), 5 SPG11, 4 SPG5, 4 cerebrotendinous xanthomatosis (CTX), 3 SPG7 and 2 SPG3A, and 10 healthy, unrelated control subjects, with similar age, sex and education participated in the study. SPG4 patients had worse performances in MOCA, FAS, FAS-cat and RAVLT when compared to controls. Most SPG4 patients presented cognitive changes not compatible with dementia, performing poorly in memory, attention and executive functions. SPG5 patients scored lower in executive functions and memory, and SPG7 patients performed poorly on memory tasks. All evaluated cognitive functions were markedly altered in CTX and SPG11 patients. The 2 patients with SPG3A performed normal on cognitive tests. Conclusions: Cognitive abnormalities are frequent in HSP, being more severe in complicated forms. However, cognitive impairments of pure HSPs might impact patients’ lives, decreasing families´ socioeconomic status and contributing to the overall disease burden.